Neurofibroma of bladder: A case report and literature review - Zhipeng Yan; Baoqun Xu; Maokun Sun; Heng Zhang; Xiaolu Sun; Lihua Li; Yulan Gao; Yunji Sun (Urology Case Reports)
To improve the understanding and treatment level of urogenital nerve fibroma by sharing the clinical manifestations, imaging features, and pathological characteristics of a case of urogenital nerve fibroma.The patient was a middle-aged male with initial symptoms of painless gross hematuria, bladder irritation, and pelvic mass. Imaging examination showed a bladder mass, and transurethral bladder tumor resection was performed to reduce the tumor. Pathology was confirmed to be bladder neurofibroma. After 6 months of surgery, follow-up examination showed a significant reduction in tumor volume and no recurrence. The successful diagnostic and therapeutic experience of this case can be referenced for clinical practice.